Covid-19 in the Italian press - Marcol-Cacoń, Lucyna; Dykta, Dominika (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
This article aims to present how the COVID-19 has influenced the current texts of the Italian press. We pay attention to the vocabulary relating to the pandemic in the most characteristic linguistic phenomena of the Italian language. We support the theoretical questions with examples taken from Italian newspapers (current articles). The goal of our work is to characterize la vivacità espositiva, the captivating titles, their nominalization, the phraseological verbs, the direct speech, cleft sentence, il c’è presentativo, la dislocazione a sinistra, whose purpose is mainly to simplify the language of the press and to make the text more attractive. The presence of neologisms, plasticisms, acronyms, and war metaphors are particularly characteristic of the press language during the pandemic. The language of the press occupies a special place among the sectoral languages, currently undergoing changes also due to the world situation during the pandemic.